German-language Popular Music Studies in Germany, Austria and Switzerland - Martin Pfleiderer (IASPM Journal, 2011)
Following the foundation of IASPM in 1981, the German ASPM (Arbeitskreis Studium Populäre Musik e.V.) was established in 1984. Although there is a free dialogue with IASPM, the organizations operate independently. In Germany, Austria and Switzerland, a variety of courses are offered in popular music studies, although often by young tutors, many of whom are doctoral students, which means that the field still has some way to go to become firmly established in the academic world. In addition, German-speaking academic communities read English-language publications but few publish their research papers in English, in international journals. Nevertheless, there is no big gap between the issues of popular music research in Germany and in the predominant Anglo-American academic discourses, due to central themes concerning popular music that bridge the frontiers of nation-states and national culture, such as globalisation, world music, or performance and media studies.